The Validation Analysis Methodology to Determine the Cadmium, Indium and Impurities Concentration in Nuclear Grade Silver-indium-cadmium Alloys - Guilherme Costa de Oliveira (Brazilian Journal of Radiation Sciences, 2022)
This work aims optimized to set up and an analytical method for a reliable determination of silver-indium-cadmium alloy constituents and their impurities through the use of ICP OES (Inductively coupled plasma optical emission spectrometer). It has greater precision, accuracy, and sensitivity when compared to the traditional methodology. The validation process was carried out according to INMETRO’s (Instituto Nacional de Metrologia, Qualidade e Tecnologia) Analytical Method Validation Guidance.